Avaliação da agricultura de baixa emissão de carbono e inteligente ao clima no Brasil - Bezerra, Filomena Nádia Rodrigues (2022)
The challenge of agriculture permeates the incompatibility between agricultural systems traditions and socio-environmental sustainability. It should be noted that there is an aggravating factor that comes from climate change, posing a major threat to agriculture, food security and the livelihoods of millions of people on a global scale. Given this situation, this thesis aims to measure the effects of climate instability in the face of low-carbon and climate-smart agriculture strategies in Brazil. Specifically, we sought to: i) Evaluate the impact of the Low Carbon Agriculture Program (ABC Program) on the value of agricultural production by emission of Greenhouse Gases (GHG) in Brazil; ii) Estimate the effect of climate instability on the value of agricultural production per hectare (VBP/ha) in the Brazilian states; and iii) Assess the level of implementation of the three pillars related to the Climate Smart Agriculture (CSA) approach in the municipalities of Bahia, Pernambuco and Rio Grande do Norte. The following methodological procedures were used according to the objectives: (i) Synthetic Control method; (ii) Panel Data method; and (iii) measured in three stages: I- Analysis of the sustainability of agricultural productivity and income - Geometric Growth Rate (GCT) and crop projections via the Autoregressive Integrated Moving Average model (ARIMA); II- Analysis of the resilience of agriculture to the climate - Factor Analysis; and III- Measure GHG emissions considering the agricultural practices adopted - Panel Data method. The results showed that the ABC Program in Brazil had a positive effect in increasing the gross value of production by GHG emissions in the agricultural sector. Although credit distribution is concentrated in the Midwest and Southeast regions. As for the effects of climate instability on the VBP/ha, the results showed that the increase in rainfall in years of occurrence of La Niña events increased the VBP/ha by 0.08%. On the other hand, the increase in temperature in irrigated areas caused a reduction of -1.82% in VBP/ha. The increase in CO2 fertilization in states that have irrigated areas increased the VBP/ha by 0.13%. However, if GHG emissions exceed the appropriate limits for assimilation by plants, the effect will be negative. The fire-scarred area showed no significant effect. As for the CSA approach, the results of Pillar I pointed to a trend of productivity and income growth for the states of Bahia and Rio Grande do Norte, indicating sustainability both in the short and long term, with the exception of Pernambuco; in Pilar II it was possible to conclude that only the state of Pernambuco showed resilience of agriculture to the climate; Pillar III: the municipalities of the analyzed states are below the desired standards, since conventional practices prevail that are not adapted to conservation agriculture. In summary, the formulation of climate policies should prioritize the technical training of farmers and the dissemination of best practices that adopt the principles related to conservation, mitigation, adaptation and resilience of agriculture to the climate, with the aim of reducing risks in taking decision.